Riba, profit rate, Islamic rate, and market equilibrium - Yusoff, Mohammed (2013)
Muslim economists have suggested the profit rate to replace riba in an Islamic economic system. While this suggestion is a step in the right direction, it still has problem since not all profits are halal, as for example, profits from gaming and liquor businesses are definitely haram. This paper discusses the concept of riba and differentiates it from the profit rate and Islamic rate. As riba is prohibited in Islam, this paper explains the concepts of Islamic rate, which is lawful in Islam as it is directly derived from the profits of halal business activities. The Islamic rate is the clearing mechanism in the money market and good market. The paper has also derived the money market equilibrium and good market equilibrium conditions or the IS-LM framework which can be used to analyse the efficacy of monetary and fiscal policy in an Islamic state. In order to clear the notion that the conventional banking system has been dictating the decision makings in the Islamic banking system in Malaysia, the paper uses the Toda-Yamamoto technique of Granger causality test to see the causality between the Islamic investment deposit rates of Islamic banking and the fixed deposit rates of the conventional banking. The results are not conclusive as a number of Islamic investment deposit rates have caused the fixed deposit rates while some fixed deposit rates cause Islamic investment deposit rates, and yet some others show that there are no causality between the two types of rate.